Far Lateral Craniotomy Closure Technique for Preservation of Suboccipital Musculature - Ali, Muhammad Salman; Magill, Stephen T.; McDermott, Michael W. (Journal of Neurological Surgery Part B: Skull Base, 2020)
The far lateral approach is used for accessing pathology at the craniovertebral junction but can be complicated by postoperative suboccipital muscle atrophy. In addition to significant cosmetic deformity, this atrophy can lead to head and neck pain and potentially could contribute to cranio-cervical instability. To address this issue, the senior author began using a single myocutaneous flap without a muscle cuff and securing it directly to the bone using predrilled holes in the bone that resemble a chevron. The method is described and illustrated with an example case. Results from seven consecutive cases are reported since the technique was adopted. Muscle atrophy was measured by calculating area at the level of the occipital condyle and compared with the contralateral side. No significant differences were noted. In conclusion, we have found this to be an excellent closure technique and wanted to present our initial results for consideration by other skull base surgeons.
Keywords: far lateral; transcondylar; muscle atrophy; modified far lateral; extreme lateral; technique